2018
DOI: 10.1007/s00417-018-4052-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of visual outcomes, reading skills, contrast sensitivity, and patient satisfaction with two models of trifocal diffractive intraocular lenses and an extended range of vision intraocular lens

Abstract: All the tested IOLs provided good visual outcome, reading performance, and spectacle independence after cataract surgery. While trifocal IOLs gave better near visual acuity results, the ERV IOL provided better contrast sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
190
6
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(231 citation statements)
references
References 33 publications
28
190
6
7
Order By: Relevance
“…6,13,14 However, visual outcomes at near have been reported to be relatively lower than those achieved with multifocal IOLs when emmetropia is the target. [15][16][17][18] In the current study, all patients achieved excellent distance and intermediate visual acuity with good near visual acuity when implanted with EDOF toric or non-toric IOLs bilaterally.…”
Section: Discussionsupporting
confidence: 51%
“…6,13,14 However, visual outcomes at near have been reported to be relatively lower than those achieved with multifocal IOLs when emmetropia is the target. [15][16][17][18] In the current study, all patients achieved excellent distance and intermediate visual acuity with good near visual acuity when implanted with EDOF toric or non-toric IOLs bilaterally.…”
Section: Discussionsupporting
confidence: 51%
“…11,15,16,[18][19][20][21] This technology is called Enlighten ® Optical Technology by the manufacturer (Alcon Laboratories, Inc.) and there has been a great acceptance and patient satisfaction with this intraocular lens as the intermediate vision is very comfortable and sharp. 11,15,16,[19][20][21][22][23][24][25][26][27][28][29][30] The diffractive zone is also in the central portion and occupies 4.5 mm of the optical zone. It adds a negative spherical aberration of −0.1 μm on the anterior face of the lens to compensate the positive spherical aberration generated by the average human cornea.…”
Section: Introductionmentioning
confidence: 99%
“…It also uses a proprietary achromatic diffractive echelette design to correct chromatic aberration, also enhancing CS and has exhibited satisfactory results for near, intermediate and far vision in diverse previous studies. 15,20,21,28,…”
Section: Introductionmentioning
confidence: 99%
“…reported that both EDOF and trifocal IOLs resulted in more frequent halos than did monofocal IOLs [19]. Five studies reported no difference in halos between EDOF and trifocal IOLs [9,10,19,22,23].…”
Section: Contrast Sensitivitymentioning
confidence: 97%
“…Seven studies [10,18,[20][21][22][23][24] reported contrast sensitivity and the results are summarized in Table 3.…”
Section: Contrast Sensitivitymentioning
confidence: 99%